Depression in the physically ill - Hanwella, Raveen; De Silva, V. (Ceylon Medical Journal, 2008)
The risk of depression is increased in many medical and surgical conditions. Specific serotonin reuptake inhibitors are generally recommended as first line treatment in the physically ill. Care must be taken in prescribing antidepressants in the physically ill, because of side effects, hepatic and renal impairment, and potential for drug interactions.
Keywords: depression; antidepressants; continuing medical education; physically ill; management